Nanoemulsion formulation of lemongrass essential oil using Pseudomonas-derived rhamnolipids for targeted phytopathogen suppression - Gandi, Manemegalai Suria; Ahmad, Khairulmazmi; Mokhtar, Noriznan; Zakaria, Mohd Rafein (Springer Science and Business Media Deutschland GmbH, 2025)
The present study focuses on developing a bio-based oil-in-water (O/W) nanoemulsion formulation for pesticide application. Lemongrass (Cymbopogon flexuosus) essential oil (EO) was incorporated as the active agent, and rhamnolipid (RL) biosurfactant served as the emulsifier. RL exhibited more than 50% emulsification activity in all tested hydrophobic substrates and, at 1 g/L, it demonstrated a lower surface tension value (30.15 mN/m) than its synthetic counterpart, sodium dodecyl sulfate (SDS) (32.87 mN/m). Lemongrass EO exhibited a minimum inhibitory concentration MIC of 3.2 mg/mL against Rigidoporus microporus and Fusarium oxysporum, and 4.0 mg/mL against Ganoderma boninense, with minimum fungicidal concentration (MFC) ranging from 3.2 to 4 mg/mL. Nanoemulsions stabilized with RL were prepared at varying oil-to-surfactant ratios (OSR) using ultrasonication. The optimized formulation (A2) was prepared at an OSR of 1:2, corresponding to 10% oil (v/v) of the total emulsion volume. Formulation A2 exhibited a mean particle size of 119.95 nm with a polydispersity index (PDI) of 0.35. The formulation also showed favourable physicochemical properties, including a zeta potential of − 27.63 mV, viscosity of 22.56 mPa/s, and surface tension of 23.9 mN/m, along with good storage stability. The sonication time was optimized to 10 min to achieve minimal droplet size and PDI. Overall, this study demonstrates that RL-stabilized lemongrass EO nanoemulsions can serve as an eco-friendly nanofungicide, offering a sustainable alternative to synthetic fungicides in managing fungal phytopathogens.